ANALISIS IMPLEMENTASI MANAJEMEN RISIKO PADA PEMBANGUNAN MUSEUM DAN GALERI SENI SBY*ANI DENGAN HIRARC (HAZARD IDENTIFICATION, RISK ASSESSMENT, AND RISK CONTROL) - Tahta Athallah Nur Cahyo; Agung Sutarto (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
One of the obstacles when working on a construction site is industrial accidents. This is evidenced by the number of accidents at work in 2020. The number increased from 85,109 at the beginning of 2020 to 108,573. This study aims to define implementing the K3L risk management system and measures to minimize emerging risks. This study used descriptive qualitative methods. The data analysis process is conducted through Hazard Identification, Risk Assessment, and Risk Control (HIRARC), which includes three steps: risk identification, risk analysis or assessment, and risk mitigation. Data was collected by distributing checklist questionnaires to 30 employees and interviewing HSE project managers. Data were obtained from various sources relevant to the study. A study of the project identified 29 risk variables. According to the processed data, when constructing a roof with a risk index of 5.90, it is known that the most significant risk appears in the variable risk of falling from a high place. On the other hand, the slightest breakage risk of the Sling TC hazard variable is 2.56 when read from cast steel structures with the resulting hazard index. It is essential to monitor risk as a form of continuous improvement to minimize risk when suppressing or reducing its likelihood and severity